2011
DOI: 10.1074/jbc.m110.156018
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biological Properties of the Drosophila Insulin-like Peptide 5 Show Evolutionary Conservation

Abstract: We report the crystal structure of two variants of Drosophila melanogaster insulin-like peptide 5 (DILP5) at a resolution of 1.85 Å . DILP5 shares the basic fold of the insulin peptide family (T conformation) but with a disordered B-chain C terminus. DILP5 dimerizes in the crystal and in solution. The dimer interface is not similar to that observed in vertebrates, i.e. through an anti-parallel ␤-sheet involving the B-chain C termini but, in contrast, is formed through an anti-parallel ␤-sheet involving the B-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 66 publications
(62 reference statements)
3
86
0
Order By: Relevance
“…Wen et al (Wen et al, 2010) showed that A. aegypti ILP3 bound to MIR in isolated ovary membranes with much higher affinity than did ILP4 or bovine insulin, indicating that the MIR varies in its affinity for endogenous ILPs as well as for mammalian insulin. Similarly, the Drosophila melanogaster insulin receptor can respond to different ILP ligands, as shown by the ability of DILP5 isoforms and IGFs to competitively displace human insulin from the fruit fly insulin receptor (Sajid et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Wen et al (Wen et al, 2010) showed that A. aegypti ILP3 bound to MIR in isolated ovary membranes with much higher affinity than did ILP4 or bovine insulin, indicating that the MIR varies in its affinity for endogenous ILPs as well as for mammalian insulin. Similarly, the Drosophila melanogaster insulin receptor can respond to different ILP ligands, as shown by the ability of DILP5 isoforms and IGFs to competitively displace human insulin from the fruit fly insulin receptor (Sajid et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…IPCs are found in the anterior brain and consist of seven cell bodies in each brain lobe, positioned bilaterally in both the larva and the adult. Ilps, which exhibit structural similarity to human insulin, bind and activate a highly conserved insulin receptor that can also be activated by insulin (Nässel et al, 2015;Sajid et al, 2011;Sekine et al, 2010). Accordingly, IPCs and Ilps regulate metabolic homeostasis and obesity in a manner analogous to that of the pancreatic β-cell; thus, IPC ablation leads to hyperglycemia (Rulifson et al, 2002).…”
Section: Neurosecretory Cellsmentioning
confidence: 99%
“…evolutionary conserved and ubiquitous factors historically involved in the regulation of energy metabolism, have been the subject of thorough investigations. In humans, ILPs include insulin, IGF1, IGF2, and seven relaxin-related peptides, which share the same basic fold (Sajid et al 2011). In the present review, the term 'ILP' will be used to indicate insulin and IGFs, whereas relaxin-related peptides will not be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…IGF1 production in the liver is stimulated by GH (Blethen et al 1981, Madsen et al 1983. IGFs have characteristics of both hormones and tissue growth factors, and consequently, they can induce both local and systemic responses (Blundell et al 1978, Sajid et al 2011. Tissues that classically respond to IGFs preferentially express the IGF1R, and nonclassic target tissues including cancer cells express both the latter receptor and IR-A genes and may display hybrid receptors as well, which probably account in carcinogenesis and chemoresistance (Artim et al 2012, Pierre-Eugene et al 2012.…”
Section: Introductionmentioning
confidence: 99%